Distinction Principle and The Use of Autonomous Weapons Systems in Armed Conflict - Kumtrai, Damorn (Connexion: Journal of Humanities and Social Sciences, 2021)
There has been widespread use of the autonomous weapon systems on the field of battle. The use of weapon in this pattern trends to increase in the future. In term of academic purpose, the concern has been on the consistency between the use of the autonomous weapon systems and the international humanitarian law, especially the impact on the civilians and non-military targets. This article aims to examine problems in applying the distinction rule under the humanitarian law to the use of autonomous weapons systems and the approach to develop such principle by analyzing the legal principles under Geneva Conventions, 1949 and other relevant laws, the application of international laws by the International Court of Justice, the international seminar reports, the reports of international organizations and the academic journals. The study finds that the complication of technology leads to the mistakes in using the Autonomous Weapons and the pattern of use that is not clear between civilian and military targets brings about problem in controlling the use of autonomous weapon systems. The recommendation is to develop measures to examine the use of autonomous weapons systems before use in order that the use of autonomous weapons be in line with the Distinction Principle and builds up measures in intervening the use of autonomous weapons systems in the needed cases in order not to affect the target beyond the military purpose.